2020
DOI: 10.1080/10872981.2020.1764740
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on the undergraduate medical curriculum

Abstract: The coronavirus pandemic has impacted medical education globally. As universities seek to deliver medical education through new methods of modalities, this continuing of education ensures the learning of the future workforce of the NHS. Novel ways of online teaching should be considered in new medical curricula development, as well as methods of delivering practical skills for medical students online. ARTICLE HISTORY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
294
0
19

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(318 citation statements)
references
References 2 publications
5
294
0
19
Order By: Relevance
“…During this challenging time, the academic leadership presented guidelines/protocols to conduct course delivery and assessment in a remote environment which were found to be helpful for students and staff [ 16 19 ]. Medical schools and faculty utilized novel methods of delivering education, which need to be adopted much earlier to teach “adult learners” [ 28 , 29 ]. Online delivery of courses has the potential to enhance student engagement, geographical accessibility, and synchronous/asynchronous learning and assessment [ 12 , 18 , 19 , 24 , 29 ].…”
Section: Impact Challenges and Opportunities Of Covid-19 On Preclinmentioning
confidence: 99%
See 2 more Smart Citations
“…During this challenging time, the academic leadership presented guidelines/protocols to conduct course delivery and assessment in a remote environment which were found to be helpful for students and staff [ 16 19 ]. Medical schools and faculty utilized novel methods of delivering education, which need to be adopted much earlier to teach “adult learners” [ 28 , 29 ]. Online delivery of courses has the potential to enhance student engagement, geographical accessibility, and synchronous/asynchronous learning and assessment [ 12 , 18 , 19 , 24 , 29 ].…”
Section: Impact Challenges and Opportunities Of Covid-19 On Preclinmentioning
confidence: 99%
“…Many medical schools have worked to transform pedagogy by increasing online lectures of basic medical sciences, using technology to replace and enhance basic sciences and laboratory teaching, and implementing online formative and summative assessments [ 14 – 16 , 18 – 22 ]. Online lectures, flipped lectures, videos, virtual simulators, webcasting, online chatrooms, and other technologies and simulation-based teaching modalities have been used to teach preclinical courses [ 18 – 22 , 25 , 28 ]. Small group teaching in virtual team settings are found to be effective, even for some laboratory science and practical training contents [ 22 , 28 ].…”
Section: Impact Challenges and Opportunities Of Covid-19 On Preclinmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study showed that the mean of ve subscales of effective e-learning, including quality of content, effective interaction, supporting systems, the management of virtual classes and management of the motivations was in the medium range. Although many universities in the world started to use platforms such as Zoom for online education, that made the interaction between students and teacher easier [8], the majority of medical universities in Iran relied on virtual education using a website called NAVID that was not feasible for mutual interaction. In NAVID system teachers were able to record their voice on slides and put those slides on the website.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time where online PAL is highly needed and desired instructional tool, it has its own challenges as well (10). The desire to make online PAL as an effective instructional tool in future, the study has explored these challenges.…”
Section: Discussionmentioning
confidence: 99%